Changes in left ventricular size, geometry, pump function and left heart pressures during healthy aging - Roger E Peverill (Reviews in Cardiovascular Medicine, 2021)
There are cross-sectional and longitudinal imaging studies using echocardiography and cardiac magnetic resonance in healthy adult subjects which have demonstrated associations of left ventricular (LV) structure and pump function with age. There are also cross-sectional data regarding the relationships of age with invasively measured left heart chamber pressures. Increasing age is associated with decreases in LV end-diastolic volume (LVEDV), end-systolic volume (LVESV), end-diastolic length (LVEDL), stroke volume (SV) and cardiac output (CO), and increases in relative wall thickness (RWT), LV mass/LVEDV ratio (LVMVR) and ejection fraction (LVEF). Older age is not accompanied by a change in mean left atrial (LA) pressure, but there is both direct and indirect evidence which suggests that LV end-diastolic pressure (LVEDP) increases with age. LVEDV remains lower in older than younger subjects during fluid infusion and the resulting increases in LA pressure. The combination of an increase in LVEF with reductions of both SV and CO demonstrates an age-related increase in divergence between LVEF and LV pump function. A lower LVEDV in older compared to younger subjects can be characterized as an aging-related decrease in LV capacity, with the higher LVEDP in older subjects also indicating a reduction of preload reserve.